OBTAINING PREFORMED PEACHES TREES - PICOLOTTO, Luciano; BIANCHI, Valmor João; FISCHER, Doralice Lobato Oliveira; PASA, Mateus da Silveira; GAZOLLA NETO, Alexandre; SCHMITZ, Juliano Dutra; ZUCHI, Jacson; PEREIRA, Ivan dos Santos; ROCHA, Moacir da Silva; FACHINELLO, José Carlos (Scientia Agraria, 2007)
Benefits of preformed peaches trees include the facility at the initial management of the trees, early fruit production and reducing labor. For these reasons, this experiment aimed to evaluate the different training systems, spacing and cultivars on the production of preformed peach trees. The training systems used were central leader, vase and epsilon. The peaches trees were planted at 100 x 10 cm and 100 x 25 cm spacing. ‘Maciel’, ‘Granada’ and ‘Eldorado’ grafted on ‘Capdeboscq’ were the cultivars utilized. The variables assessed were trunk diameter, difference between rootstocks and cultivar trunk diameter, which were measured above and below the grafting point, height and tree volume, number and branches length. The development of preformed trees was feasible for ‘Marciel’ using the vase and central leader training system. The 100 x 10 cm was suitable to the formation of preformed trees.